Effect of propofol versus midazolam on short-term outcomes in patients with sepsis-associated acute kidney injury - Li, Yuanjie; Guo, Taipu; Yang, Zhenkun; Zhang, Rui; Wang, Zhi; Li, Yize (Frontiers in Medicine, 2024)
Background: Propofol and midazolam are commonly used sedative drugs in mechanically ventilated patients in the Intensive Care Unit (ICU). However, there is still a lack of relevant studies exploring the influence of midazolam and propofol on the prognosis of patients with Sepsis-associated Acute Kidney Injury (S-AKI).A statistical analysis was conducted on 3745 patients with S-AKI in the Medical Information Mart for Intensive Care IV database. The patients' baseline characteristics were grouped based on the use of either propofol or midazolam as sedatives. Cox proportional hazards models, logistic regression models, and subgroup analyses were used to compare the effects of propofol and midazolam on the short-term prognosis of S-AKI patients, including 30day mortality, ICU mortality, and duration of mechanical ventilation.In the statistical analysis, a total of 3745 patients were included, with 649 patients using midazolam and 3096 patients using propofol. In terms of the 30-day mortality, compared to patients using midazolam, S-AKI patients using propofol had a lower ICU mortality (hazard ratio = 0.62, 95% confidence interval: 0.52-0.74, P < 0.001), lower 30-day mortality (hazard ratio = 0.56, 95% confidence interval: 0.47-0.67, P < 0.001), and shorter mechanical ventilation time (odds ratio = 0.72, 95% confidence interval: 0.59-0.88, P < 0.001). Kaplan-Meier curves showed lower survival probabilities in the midazolam group (P < 0.001). Subgroup analyses showed that propofol was strongly protective of short-term prognosis in older, male, smaller SOFA score CCI score, no heart failure, and comorbid chronic kidney disease patients with S-AKI.Compared to midazolam, propofol was considered a protective factor for short-term mortality risk and ICU mortality risk in S-AKI patients. Additionally, S-AKI patients using propofol had a lower risk of requiring prolonged mechanical ventilation. Overall, propofol may be more beneficial for the short-term prognosis of S-AKI patients compared to midazolam.